Linking mangroves and fish catch: a correlational study in the southern Caribbean Sea (Colombia) (2020)
ABSTRACT: Mangroves provide habitat to a variety of fish species, potentially enhancing fish production in small scale fisheries. Fish production ecosystem services have been correlated with mangrove area and perimeter in many tropical locations; however, nothing has been published linking small-scale fish catch and mangrove attributes in the southern Caribbean Sea. We correlated environmental variables with experimentally-derived catch per unit effort (CPUE) and richness of fishes in the Colombian southern Caribbean Sea, an area not directly connected with other productive coastal habitats. Concurrently, we measured mangrove attributes (area, perimeter, above-ground carbon), water quality (salinity, total dissolved solids), and water column productivity parameters (chlorophyll a, seston, zooplankton biovolume). Mangrove area and zooplankton biovolume were the main factors influencing fish species richness. Mangrove area was positively correlated with catches for three of the most common fish species in the local artisanal fishery: Ariopsis canteri Acero P, Betancur-R, and Marceniuk, 2017, Mugil incilis Hancock, 1830, and Sciades proops (Valenciennes, 1840), which represent about 22% of the total regional annual catch. Our results suggest causal links between mangrove habitat and fishery production through a mangrove trophic contribution. Ariopsis canteri appears to be a mangrove-dependent species and M. incilis a mangrove associated species. These results support managing or preserving mangroves in the most extensive areas in the southern Caribbean to sustain small-scale fishery resources used mainly for community sustenance where alternative resources are limited.